Preterm Delivery and Low Birth Weight Among Neonates Conceived With Intracytoplasmic Sperm Injection Compared With Conventional In Vitro Fertilization. Issue 2 (February 2018) - Keyhan, Sanaz; Truong, Tracy; Li, Yi-Ju; Jackson-Bey, Tia; Eaton, Jennifer L.
Abstract : OBJECTIVE: To examine the prevalence of prematurity and low birth weight (LBW) among singletons conceived with intracytoplasmic sperm injection (ICSI) compared with those conceived with conventional in vitro fertilization (IVF). METHODS: Using the Society for Assisted Reproductive Technology Clinic Outcomes Reporting System, we conducted a retrospective cohort study of women undergoing a first, fresh autologous ICSI or conventional IVF cycle from 2004 to 2013. Singleton live births were included in the analysis. Primary outcomes were preterm delivery and LBW. Secondary outcomes were very preterm delivery, preterm LBW, term LBW, and very LBW. Logistic regression models and propensity score matching were used to compare perinatal outcomes between ICSI and IVF cycles. Subset analyses were performed after stratification by sperm source, male factor infertility, and female prognosis. RESULTS: Of the 90, 401 cycles included in the analysis, ICSI was used in 60, 719 (67.2%) and conventional IVF was used in 29, 682 (32.8%). After propensity score matching and covariate adjustment, the two groups had similar odds of preterm delivery (adjusted odds ratio [OR] 1.02, 95% CI 0.89–1.18) and LBW (adjusted OR 0.92, 95% CI 0.78–1.10). Using the matched data set, subset analyses demonstrated no significant association between the method of fertilization and the examined perinatal outcomes. CONCLUSION: Rates of preterm delivery and LBW were similar between pregnancies conceived with ICSI and conventional IVF after propensity score matching and stratifying by baseline patient characteristics. Previously reported differences in these outcomes were likely secondary to patients' inherent risk factors rather than the fertilization procedure itself. Abstract : Among singletons conceived with assisted reproductive technology, the method of fertilization is not significantly associated with prematurity or low birth weight.